Implementasi Sistem Transmisi Data Sensor Healthcare Berbasis Zigbee Dengan Protokol Ad-hoc On Demand Distance Vector - Satria Kencana P. Kacaribu; Rakhmadhany Primananda; Agung Setia Budi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Sensor Network is a technology that has been widely researched, one of which is in the field of health (healthcare). This technology is used for health monitoring and intensive patient monitoring. Based on intensive care room data from RSUP Dr. In the July-September 2014 period there were 239 intensive care patients. Therefore, a system that can work efficiently in multi-patient monitoring is needed. Use Ad-hoc On-Demand Distance Vector (AODV) routing protocol to manage route search for AODV is needed only when there is a routing request. Zigbee can be used in areas with difficult environmental conditions with a transfer speed up to 250 Kbps. WiFi uses an overhead frame measuring 34 bytes and consumes 400 mA when transmitting and 20 mA when standby, while ZigBee uses an overhead frame measuring only 2-7 bytes and consumes 28-44 mA when transmitting and has a sleep mode to save energy . This researched applies a routing mechanism where the coordinator available to sending and receiving packets through the router node. Router nodes can receiving and forwarding data packets to end devices and coordinators. End devices can receiving and sending data packets to the coordinator. This mechanism using four scenarios produces an average end-to-end delay in 100 meters distance is 4.209 seconds. This mechanism with four scenarios results in convergence time in 100 meters distance is 5.293 seconds.